Współpraca pomiędzy dwujęzycznym przedszkolem a uniwersytetem jako narzędzie rozwoju wszystkich uczestników kooperacji - Bielicka, Małgorzata (Neofilolog, 2025)
The main aim of this paper is to highlight the significant scientific, research, teaching, and practical potential that arises from collaboration between research institutions and educational establishments. The unusually low number of studies conducted on schoolchildren in Poland, is highlighted and attributed to insufficient collaboration between educational institutions and research entities. The cooperation between the Polish-German Bilingual Kindergarten „Ene due Rabe” and the Institute of Applied Linguistics at Adam Mickiewicz University is introduced. The results of this collaboration are presented in detail, including numerous published academic articles, scientific monographs, conference papers, student internships, as well as workshops for teachers and parents. The final section explains how these forms of cooperation have contributed to the professional development of all parties involved.